Narrative Review: Type 2 Diabetes Causes - Amanda Shelvia Savitri (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Indonesia is seventh rank from 10 countries with the highest diabetic patients based on the International Diabetes Federation in 2020. One of the research result shows that women have higher risk type 2 diabetes (T2D) than men, because there is difference in body tissues where women have more adipose tissue. The purpose of this literature review is to analyze genetic factors who caused T2D. This literature research uses a narrative review design. The keywords to search the article are type 2 diabetes, type 2 diabetes factors, genetic type 2 diabetes, and factors that affect type 2 diabetes. The conclusions of causes of T2D are heredity, obesity, age, gender, education, lifestyle, food, stress, socio economic status and physical activity.